2022
DOI: 10.1212/wnl.0000000000200358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Race on Prediction of Brain Amyloidosis by Plasma Aβ42/Aβ40, Phosphorylated Tau, and Neurofilament Light

Abstract: Objective:To evaluate whether plasma biomarkers of amyloid (Aβ42/Aβ40), tau (p-tau181 and p-tau231) and neuroaxonal injury (neurofilament light chain [NfL]) detect brain amyloidosis consistently across racial groups.Methods:Individuals enrolled in studies of memory and aging who self-identified as African American (AA) were matched 1:1 to self-identified non-Hispanic White (NHW) individuals by age, APOE ε4 carrier status and cognitive status. Each participant underwent blood and cerebrospinal fluid (CSF) colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 56 publications
7
96
0
Order By: Relevance
“…The rapid development of ultrasensitive assays makes it possible to predict the levels of proteins associated with pathological AD in blood. Some plasma biomarkers have been shown to correlate closely with CSF biomarkers and imaging markers 3,4 . The core blood biomarkers of AD include Aβ42 (or Aβ42/40 ratio), phosphorylated tau181 (p‐tau181), neurofilament light chain (NfL), and total tau (T‐tau), which reflect Aβ pathology, tau pathology, and neuronal damage, respectively 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid development of ultrasensitive assays makes it possible to predict the levels of proteins associated with pathological AD in blood. Some plasma biomarkers have been shown to correlate closely with CSF biomarkers and imaging markers 3,4 . The core blood biomarkers of AD include Aβ42 (or Aβ42/40 ratio), phosphorylated tau181 (p‐tau181), neurofilament light chain (NfL), and total tau (T‐tau), which reflect Aβ pathology, tau pathology, and neuronal damage, respectively 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Some plasma biomarkers have been shown to correlate closely with CSF biomarkers and imaging markers. 3,4 The core blood biomarkers of AD include Aβ42 (or Aβ42/40 ratio), phosphorylated tau181 (p-tau181), neurofilament light chain (NfL), and total tau (Ttau), which reflect Aβ pathology, tau pathology, and neuronal damage, respectively. 5,6 Various experimental results have shown that lower plasma Aβ42/Aβ40 ratio was associated with higher amyloid cortical burden, 7,8 faster Aβ accumulation rates, 9 greater cognitive declines, 10,11 and increased risk of developing AD dementia at follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…ADNI includes a selective population of highly educated, mostly white participants, generalizable to current clinical trials that have a similar population profile but do not represent a diverse general population. Thus, it would be highly desirable to reproduce our findings in a more diverse population-based cohort 45, 46 . Furthermore, the use of different blood assays for measuring the plasma biomarkers could lead to different results.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, analytes may have differential performance based on the disease stage of the cohort under investigation. In cohorts of cognitively normal individuals, single molecule array (Simoa) measures of p‐tau181 may be less accurate in the detection of PET amyloid status whereas mass spectrometry measures of Aβ42/Aβ40 perform relatively well 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…In cohorts of cognitively normal individuals, single molecule array (Simoa) measures of p-tau181 may be less accurate in the detection of PET amyloid status whereas mass spectrometry measures of Ab42/Ab40 perform relatively well. 20,21 Although multiple studies have examined the relationship of cognitive decline with either plasma Ab42/Ab40 [22][23][24] or plasma NfL, 15,[25][26][27] it is unclear whether plasma measures of Ab42/Ab40 or NfL perform similarly to CSF measures of these analytes. Further, there are major differences in assay performance, especially for plasma Ab42/Ab40 assays, 28,29 and there have not been any wellpowered studies of cognitive decline as predicted by highperformance measurements of plasma Ab42/Ab40.…”
Section: Introductionmentioning
confidence: 99%